The Effect of Alkaline Water on Blood Glucose Diabetic White Rates. - Ramadhani, Dhia; Ediningsih, Endang; Ayusari, Amelya Augusthina (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Alkaline water has high pH level and work as antioxidant that could repair the damaged pancreatic beta cells caused by alloxan. This research aimed to know the effect of alkaline water on blood glucose in diabetic white rats induced by alloxan. Methods: This was an experimental research with pre- and post-test group design. The subjects were thirty Wistar male white rats selected by a simple random technique. They were divided into 2 groups, control group (aquadest group), and treatment group given alkaline water dosed 23 ml perday. Blood glucose were measured by stript test at the first day as GDP 1, at the fifth day after induced by alloxan as GDP 2, and the last, after treatment at the twelfth day as GDP 3. The data were analyzed by Anova test followed by Post Hoc Test using SPSS for Windows Release 20 program. Results: This research showed that there was significant difference of GDP 3 betweenaquadest and alkaline group (p=0,00) by independent t test.There was no significant difference between GDP 1 and GDP 3 both group by dependent t test. Conclusion: It concluded that alkaline water was able to decrease the blood glucose level on diabetic white rates induced by alloxan. Keywords: alkaline water, blood glucose level, antioxidantÂ